2010
DOI: 10.1161/circulationaha.109.905471
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective and Antiapoptotic Effects of Heme Oxygenase-1 in the Failing Heart

Abstract: Background-Heme oxygenase-1 (HO-1) is an inducible stress-response protein that imparts antioxidant and antiapoptotic effects. However, its pathophysiological role in cardiac remodeling and chronic heart failure (HF) is unknown. We hypothesized that induction of HO-1 in HF alleviates pathological remodeling. Methods and Results-Adult male nontransgenic and myocyte-restricted HO-1 transgenic mice underwent either sham operation or coronary ligation to induce HF. Four weeks after ligation, nontransgenic HF mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
219
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(236 citation statements)
references
References 41 publications
14
219
0
3
Order By: Relevance
“…However, when compared to WTc sham, WTc HF animals showed an approximately 40% mortality. This is in line with previously observed mortality rates for C57BLl6 permanent coronary ligation models in both our laboratory and others [63,92]. Interestingly, in postinfarction HF, we found that ablation of either TNF receptor in the inflammatory cell compartment improved survival significantly over WTc HF animals (80% vs. 60%).…”
Section: Survival Benefitsupporting
confidence: 92%
See 2 more Smart Citations
“…However, when compared to WTc sham, WTc HF animals showed an approximately 40% mortality. This is in line with previously observed mortality rates for C57BLl6 permanent coronary ligation models in both our laboratory and others [63,92]. Interestingly, in postinfarction HF, we found that ablation of either TNF receptor in the inflammatory cell compartment improved survival significantly over WTc HF animals (80% vs. 60%).…”
Section: Survival Benefitsupporting
confidence: 92%
“…Under Trichrome (for collagen) using standard histologic techniques [63,92]. The degree of tissue fibrosis (blue-green stain) was assessed using Metamorph…”
Section: Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…4, E-G). (25,26); its expression is however obviously up-regulated in different types of cancer, as it is associated with promotion of tumor cell survival (27,28). In this study, we primarily proved that HO-1 was induced by NHE1 activation.…”
Section: Ho-1 Induced By Nhe1 Was Mediated By Pkc-␤-activated P38-mapmentioning
confidence: 68%
“…HO-1 overexpression inhibits proinflammatory cytokines and chemokines under hypoxia, alleviates cardiomyocyte apoptosis and regulating pathological left ventricular remodeling (23). The anti-inflammatory properties of HO-1 may rely on its ability to degrade heme and generate bilirubin, free iron and CO, and to reverse IL-18-mediated p38a MAPK and nuclear factor-kB activation, phosphatase and tensin homolog (PTEN) induction, Akt suppression and endothelial cell death (24).…”
Section: Heme Oxygenase (Ho)mentioning
confidence: 99%